By the skin of their tongues : artist video scripts - Henricks, Nelson; Reinke, Steven (Toronto : YYZ Books, 1997)
Campbell, Colin ; Frenkel, Vera ; Guilbert, Michel ; Henricks, Nelson ; Hoolboom, Mike ; Kibbins, Gary ; Melnyk, Doug ; Murphy, Serge ; Peacock, Jan ; Reinke, Steve ; Sherman, Tom ; Sisler, Cathy ; Steele, Lisa
Korte biog. per kunstenaar p. 213-215
Engels
boek